Comparative Characterization of Swine Dung Vermicompost Using Two Earthworm Species - Michael Omofowa Osunde; Victor Chukwuma Ikeh; Olajumoke Olusola Adesanwo (Universitas Panji Sakti, 2026)
Despite the increasing use of earthworms for swine dung management, limited information exists on the comparative functional group composition and heavy metal reduction in vermicomposts produced by Eisenia fetida and Eudrilus eugeniae. This study characterized vermicompost from swine dung produced by Eisenia fetida and Eudrilus eugeniae. Pre-composted swine dung was vermicomposted for three months using 200 mature earthworms per 10 kg of substrate, with three replicates per species in a completely randomized design. The vermicomposts were analyzed for physicochemical properties and functional groups using Fourier transform infrared spectroscopy (FTIR). FTIR revealed the presence of -CH₂, -CH₃, -COO-, -C-O, and -C-O-C functional groups, indicating enrichment in organic acids and aliphatic compounds. Pb and Cd concentrations decreased substantially, from 32.0 and 0.07 ppm in raw dung to 7.0 and 0.004 ppm for E. fetida, and 7.0 and 0.008 ppm for E. eugeniae, respectively. These results demonstrate effective heavy metal reduction and functional group enhancement, suggesting that the produced vermicomposts may be suitable for agricultural use, subject to regulatory standards.